An evaluation of soft law as a method for regulating public procurement from a trade perspective - Jiang, Lili (2009)
This research is to evaluate soft law as a method to regulate public procurement from a trade perspective. The value of soft law is studied under this thesis according to a four-fold approach – bindingness, precision, discretion and delegation. An international legal instrument can be considered soft along one or more of the above four dimensions. Based on the reviews of the current procurement regimes, the thesis outlines the values of soft law in regulating procurement. Soft law may serve as a second-best to hard law where the latter can not be achieved. It is explained that public procurement is a sensitive subject in the sense that many states are often unwilling to give up their regulatory freedom for protectionism purposes. Soft law in terms of all the four dimensions is argued as an effective device for breaking deadlock and fostering compromises in negotiating a procurement agreement. Also, it can serve as an ‘intermediate step’ towards the formation of hard law even though this is not necessarily the case. Soft law can also be regarded as a better alternative to hard law even where the latter is attainable. Possible advantages of soft law are identified including its reduced negotiating costs; reduced implementing costs; reserved states’ regulatory autonomy for national legitimate objectives and better adaptation to changes. Meanwhile, its possible disadvantages are mentioned and possible ways of addressing these disadvantages are also suggested. Special features of procurement are identified including intrusiveness, sensitivity, complexity and constant evolution, which might be relevant for soft law’s influence in that particular area. At the end, the thesis sets out both s short-term and a long-term proposal for developing a multilateral agreement on government by use of soft law.